KAJIAN KENYAMANAN RUANG DITINJAU DARI TATA RUANG DALAM PADA BANGUNAN MUSEUM SENI RUPA DAN KERAMIK - Khotimah, Marifatul; Widiyanti (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
The existence of a museum is very important because it has the responsibility and function to preserve,foster, as well as develop the culture of society, both tangible and intangible. The Museum of Fine Arts andCeramics is located at jalan Pos kota No.2, West Jakarta Municipality, DKI Jakarta Province, Indonesia. TheMuseum, which is exactly opposite the Jakarta History Museum, displays local ceramics from various regions inthe country, from the era of the 14th-century Majapahit Empire, and from various countries around the world.Architectural planning both in terms of area and spatial arrangement is important to support the activities withinthe building. This study aims to determine the comfort level of space in terms of interior layout. The researchmethod uses qualitative methods. The results of the study show that the buildings in the fine arts and ceramicsmuseum meet building comfort standarts in terms of openings, interior layout and circulation within the building